2018
DOI: 10.12688/f1000research.13863.2
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling endometriosis-associated ovarian carcinomas using integrative proteomics

Abstract: Background: To elucidate potential markers of endometriosis and endometriosis-associated endometrioid and clear cell ovarian carcinomas using mass spectrometry-based proteomics. Methods: A total of 21 fresh, frozen tissues from patients diagnosed with clear cell carcinoma, endometrioid carcinoma, endometriosis and benign endometrium were subjected to an in-depth liquid chromatography-tandem mass spectrometry analysis on the Q-Exactive Plus. Protein identification and quantification were performed using MaxQuan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In proteomics, distinct markers may distinguish EOVC from other histological types. Serous tumor markers such as WT1, P53, CK20, and mucinous tumor markers such as CEA and MUC2 are not often expressed in EOVC and OCCC, and EOVC–specific markers such as ER, PR, TFF3, DKK1, and MMP7 display near-exclusive expression in EOVC ( 90 ). Current studies have found that the status of WT1, P53, Napsin-A are helpful in reducing the rate of misdiagnosis of EOVC ( 88 , 89 , 91 , 92 ).…”
Section: Molecular Characteristics Of Eovcmentioning
confidence: 99%
“…In proteomics, distinct markers may distinguish EOVC from other histological types. Serous tumor markers such as WT1, P53, CK20, and mucinous tumor markers such as CEA and MUC2 are not often expressed in EOVC and OCCC, and EOVC–specific markers such as ER, PR, TFF3, DKK1, and MMP7 display near-exclusive expression in EOVC ( 90 ). Current studies have found that the status of WT1, P53, Napsin-A are helpful in reducing the rate of misdiagnosis of EOVC ( 88 , 89 , 91 , 92 ).…”
Section: Molecular Characteristics Of Eovcmentioning
confidence: 99%
“…The spreadsheet contains the details of the identification and quantitation of all proteins across the 21 biological samples. 10.5256/f1000research.13863.d193821 ( Leung et al , 2018b)…”
Section: Data Availabilitymentioning
confidence: 99%